Experimental Investigation on the Effect of KCL and Bentonite on Shale Stability (International Journal of Current Engineering and Technology, 2015)
Shale is considered most of the time as a troublesome formation due to the problems caused while drilling using water based muds. Additionally, the shale composition which varies from one type to another has complicated the effort of developing appropriate water based mud. In light of maintaining a stable wellbore, there is need to formulate an adequate drilling mud and investigate the shale swelling and borehole instability problems associated with shale-fluid interaction. This study presents results of experimental investigation conducted on the swelling behavior of shales under static and dynamic conditions. The investigation was carried out using clean Okolobra 2 and Okolobra 5 shale samples from a Niger Delta well obtained at different depths. Dynamic swell meter was used to measure the swelling strain as a function of time at different temperatures (85, 150, and 200°F). Three types of drilling fluids were used during the investigation. Bentonite based fluids composed of varying concentrations of bentonite, barite, salt, and the KCl polymeric additives were prepared. Swelling test was conducted using cylindrical wafer (disks) of Okolobra 2 and Okolobra 5 shales. The wafers were made by compacting powder samples of both shales. The Okolobra 2 exhibited more interaction and swelling on exposure to aqueous fluids while the Okolobra 5 shales showed less swelling. Increasing temperature and fluid agitation intensify shale swelling and instability problems. This indicted that in addition to the interaction between the water molecules and shale particles, the movement of water molecules in the fluid affects the process of shale swelling.
Keywords: wellbore instability; shale swelling; swelling inhibitor additives; Mud-Shale Interaction; Oil based mud (OBM); water based mud (WBM); agitation; bentonite; KCl-Polymer